Социальные круги в свете концепции социального опосредования (Теоретико-методологический аспект) - Пипич, А.; Пипич, О. (Социология: теория, методы, маркетинг, 2008)
The article presents an approach to ‘social circles’ concept from the position based on conception of ‘social mediation’. Tracing origins of this conception up to Marks’ and Tonnies’ works, the authors draw a conclusion that ‘social mediation’ angle of vision may be useful as a guideline for application of operatinalization procedure to ‘social circles’ concept. Such an approach open the door to elaboration of the concerned notion both in theoretical and in empiric projection. From this point of view, the authors analyse some relevant aspects of Tonnies’ understanding of ‘social circles’ as well as heuristic potential of Moreno’s socio-metrical analysis of interrelations within informal groups. The attempt to clarify theoretical and empiric characteristics of social circles is justified by reference to necessity of discrimination of direct and indirect human interactions. Moreover, the latter ones may be seen as mediated by things, on the one hand, and by human beings as intermediaries, on the other hand. This point to some extend determines the critical fervor of the article. The authors also consider alteration of strategy of “social circle” empiric referents elaboration required in connection with understanding ‘social circles’ as ‘social lines’ associating and dissociating people in social space. In conclusions, there are summarized applications of offered approach to understanding of social circles regarding perspectives of their theoretical and empiric analysis.